Therapeutic potential and limitations of curcumin as antimetastatic agent - Dytrych, Petr; Kejík, Zdeněk; Hajduch, Jan; Kaplánek, Robert; Veselá, Kateřina; Kučnirová, Kateřina; Skaličková, Markéta; Venhauerová, Anna; Hoskovec, David; Martásek, Pavel; Jakubek, Milan (Biomedicine & pharmacotherapy, 2023)
Treatment of metastatic cancer is one of the biggest challenges in anticancer therapy. Curcumin is interesting nature polyphenolic compound with unique biological and medicinal effects, including repression of metastases. High impact studies imply that curcumin can modulate the immune system, independently target various metastatic signalling pathways, and repress migration and invasiveness of cancer cells. This review discusses the potential of curcumin as an antimetastatic agent and describes potential mechanisms of its antimetastatic activity. In addition, possible strategies (curcumin formulation, optimization of the method of administration and modification of its structure motif) to overcome its limitation such as low solubility and bioactivity are also presented. These strategies are discussed in the context of clinical trials and relevant biological studies.
Keywords: Metastasis; Neoplasms; Migrastatic agents; Curcumin; kurkumin; protinádorové látky; Humans; Tumour targeting; nádory; Antineoplastic Agents; Nanoparticles; lidé